Group counseling. - A. Hamid , Siti Zubaidah (Universiti Sains Malaysia, 1980)
Up to this point we have been concerned largely with individual counseling,. or one-to-one counseling. Before a counselor can hope to imagine to tackle the complexities of group counseling, individual counseling must be mastered.